2020
DOI: 10.1007/s00520-020-05847-6
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline, tocopherol, and sequestrectomy are effective for the management of advanced osteoradionecrosis of the jaws—a case series

Abstract: Background The aim of the present study was to evaluate the efficacy of pentoxifylline and tocopherol for the management of osteoradionecrosis of the jaws. Methods Twenty-five patients diagnosed with osteoradionecrosis of the jaws treated with pentoxifylline 400 mg + tocopherol 400 mg three times daily (tid) were evaluated. Clinical records and image tests were reviewed. All patients were previously submitted to head and neck radiation therapy and presented with a clinical and radiographic diagnosis of osteora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, differences as great as those found in our “During - Before” mean scores for Role functioning/physical (-32.8 points) and Role functioning/emotional (-18.9 points) and in OHIP14 (3.6 points) were remarkable and leave no doubt about the magnitude of these decreases after the advent of the COVID-19 pandemic. Further, it must be kept in mind that the MCID for the group-level is necessarily smaller than for the individual patient-level, because of greater measurement errors inherent to patient quality of life scores ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, differences as great as those found in our “During - Before” mean scores for Role functioning/physical (-32.8 points) and Role functioning/emotional (-18.9 points) and in OHIP14 (3.6 points) were remarkable and leave no doubt about the magnitude of these decreases after the advent of the COVID-19 pandemic. Further, it must be kept in mind that the MCID for the group-level is necessarily smaller than for the individual patient-level, because of greater measurement errors inherent to patient quality of life scores ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eighty publications were identified on the basis of the search strategy described in the Methods section. Of these, six were RCTs, [10][11][12][13][14][15] 14 were prospective studies, 3,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] and 60 were retrospective studies. The identified trials were published between 2004 and 2023.…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%
“…Nine studies of pentoxifylline and potentiation by clodronate (PENTOCLO) were identified. 19,20,26,44,59,60,69,75,77 In one controlled study, pentoxifylline was used in combination with surgery and doxycycline, which led to inconclusive results regarding the effect of pentoxifylline in mild, moderate, and severe ORN cases. 69 The remaining two prospective 19,26 and six retrospective studies 20,44,59,60,75,77 of pentoxifylline in mild, moderate, and severe ORN cases reported healing rates of 60%-100% in studies that also administered clodronate, ciprofloxacin, amoxicillin and/or prednisolone.…”
Section: Nonsurgical Management Of Ornmentioning
confidence: 99%